2017
DOI: 10.1111/gcbb.12415
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent climate impact and energy efficiency of combined heat and power production from short‐rotation coppice willow using pyrolysis or direct combustion

Abstract: A life cycle assessment of a Swedish short-rotation coppice willow bioenergy system generating electricity and heat was performed to investigate how the energy efficiency and time-dependent climate impact were affected when the feedstock was converted into bio-oil and char before generating electricity and heat, compared with being combusted directly. The study also investigated how the climate impact was affected when part of the char was applied to soil as biochar to act as a carbon sequestration agent and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…For example, Clare and colleagues [236] showed that using straw residues for gasification or coal briquettes leads to higher climate change mitigation potentials than biochar in China due to larger offsets of fossil energy. Other studies [69,151,253] reach similar conclusion with standard bioenergy systems achieving more climate benefit compared to biochar sequestration. As a general interpretation, larger climate benefits from using residues for biochar production are achieved in regions with low carbon intensity energy systems, whereas in regions with high carbon intensive energy systems, the use of residues for bioenergy is a better option as it can bring the largest emission savings.…”
Section: Life-cycle Assessment Of Biochar Systemssupporting
confidence: 61%
See 1 more Smart Citation
“…For example, Clare and colleagues [236] showed that using straw residues for gasification or coal briquettes leads to higher climate change mitigation potentials than biochar in China due to larger offsets of fossil energy. Other studies [69,151,253] reach similar conclusion with standard bioenergy systems achieving more climate benefit compared to biochar sequestration. As a general interpretation, larger climate benefits from using residues for biochar production are achieved in regions with low carbon intensity energy systems, whereas in regions with high carbon intensive energy systems, the use of residues for bioenergy is a better option as it can bring the largest emission savings.…”
Section: Life-cycle Assessment Of Biochar Systemssupporting
confidence: 61%
“…Some studies do not provide the required disaggregation of the data accross the different life-cycle stages, and in this case, only the total score is included in Figure 3 [236][237][238][239][240][241][242][243][244][245][246][247][248]. Some LCA studies define their functional unit as "per tonne of crop" or "per hectare cultivated" and did not provide conversion factors to transform their results into "per tonne of feedstock" as presented in Figure 3 [249][250][251][252][253][254][255][256][257][258][259][260]. As such, results from these studies are qualitatively discussed but not included in Figure 3.…”
Section: Life-cycle Assessment Of Biochar Systemsmentioning
confidence: 99%
“…The most common climate impact metric used in LCA is global warming potential (GWP 100 ), which is based on radiative forcing and captures the integrated impacts over a single time horizon of 100 years [31]. It does not capture the effect of timing and persistence of GHG fluxes and temporal changes in SOC [32]. It does not represent the actual impacts on ecosystems such as temperature change, sea level change or biodiversity loss.…”
Section: Introductionmentioning
confidence: 99%
“…Using a time-dependent method can counter this by expressing the climate metric as a function of time. Several studies have developed such alternative methods and applied them in LCA to capture the emissions and fluxes of carbon flows between the atmosphere, biomass and soil [17,[32][33][34]]. An absolute time-dependent climate metric such as the absolute global temperature change potential (∆Ts) developed by Ericsson et al [35] represents the impact on global mean surface temperature from emission or removal of a GHG at a particular point in time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation